Comparative transcriptome analysis of cold-tolerant and -sensitive asparagus bean under chilling stress and recovery - Miao, Mingjun; Tan, Huaqiang; Liang, Le; Huang, Haitao; Chang, Wei; Zhang, Jianwei; Li, Ju; Tang, Yi; Li, Zhi; Lai, Yunsong; Yang, Liang; Li, Huanxiu (PeerJ, 2022)
Background Low temperature is a type of abiotic stress that threatens the growth and yield of asparagus bean. However, the key genes and regulatory pathways involved in low temperature response in this legume are still poorly understood. Methodology. The present study analyzed the transcriptome of seedlings from two asparagus bean cultivars—Dubai bean and Ningjiang 3—using Illumina RNA sequencing (RNA-seq). Correlations between samples were determined by calculating Pearson correlation coefficients (PCC) and principal component analysis (PCA). Differentially expressed genes (DEGs) between two samples were identified using the DESeq package. Transcription factors (TF) prediction, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis of DEGs were also performed. Results Phenotypes and physiological indices indicated that Ningjiang 3 seedlings tolerated cold better than Dubai bean seedlings, in contrast to adult stage. The transcriptome dynamics of the two cultivars were closely compared using Illumina RNA-seq following 0, 3, 12, and 24 h of cold stress at 5 °C and recovery for 3 h at 25 °C room temperature. Global gene expression patterns displayed relatively high correlation between the two cultivars (>0.88), decreasing to 0.79 and 0.81, respectively, at 12 and 24 h of recovery, consistent with the results of principal component analysis. The major transcription factor families identified from differentially expressed genes between the two cultivars included bHLH, NAC, C2H2, MYB, WRKY, and AP2/ERF. The representative GO enrichment terms were protein phosphorylation, photosynthesis, oxidation-reduction process, and cellular glucan metabolic process. Moreover, KEGG analysis of DEGs within each cultivar revealed 36 transcription factors enriched in Dubai bean and Ningjiang 3 seedlings under cold stress. Conclusions These results reveal new information that will improve our understanding of the molecular mechanisms underlying the cold stress response of asparagus bean and provide genetic resources for breeding cold-tolerant asparagus bean cultivars.
Keywords: Asparagus bean; Sesquipedialis; RNA-seq; Cold stress; Recovery; Transcriptome